Research on the impact of fiscal environmental protection expenditure on agricultural carbon emissions - Wu, Saijun; Chen, Xueqing (Frontiers in Environmental Science, 2023)
As a large agricultural country, China's agricultural and rural greenhouse gas emissions account for about 15% of its total emissions. Studying how to reduce China's agricultural carbon emissions (ACEs) is of great strategic significance. Based on the panel data of 31 provinces (cities) in China from 2007 to 2020, this paper empirically tests the impact of fiscal environmental protection expenditure (FEPE) on ACEs. The results reveal that: FEPE has significant negative impacts on ACEs; FEPE has a heterogeneous impact on ACEs in different regions, which shows that it has a significant impact on the eastern and central regions and provinces with relatively "high" carbon emissions, while it has no significant impact on the western regions and provinces with relatively "low" carbon emissions; Further the results of mechanism analysis show that the impact of FEPE on ACEs is mainly manifested in its inhibiting effect on agricultural diesel, fertilizer and film use of carbon emissions. In light of these findings, it is imperative for the government to ensure steady and substantial investments in environmental protection. Moreover, implementing region-specific measures is essential to effectively curbing ACEs. The findings of this study offer invaluable insights that can guide the formulation of policies aimed at effectively reducing ACEs.